Contribution of Shellfish Consumption to Lower Mercury Health Risk for Residents in Northern Jiaozhou Bay, China - Lei Zhang; Lei Zhang (Bioinorganic Chemistry and Applications)
Fish and marine mammal consumption are an important pathway for human exposure to mercury. The low mercury content in shellfish poses a low mercury health risk to people who consume shellfish. The objectives of this study are to detect mercury concentrations in different species of shellfish and to calculate the mercury health risk from shellfish consumption among traditional residents near northern Jiaozhou Bay. A total of 356 shellfish samples, which comprised 7 species from 5 different places in northern Jiaozhou Bay, were collected from April to June in 2012. The average mercury content in the collected shellfish ranged from 0.024 mg·kg−1 to 0.452 mg·kg−1. A total of 44 shellfish samples (12.36%) had mercury levels exceeding the national pollution-free aquatic products limit (0.3 mg·kg−1). Generally, the viscus had the highest mercury content among all parts of the shellfish. A positive correlation between mercury content and total weight/edible part weight was found in most species of the collected shellfish. The results showed that shellfish consumption resulted in the lower risk of mercury exposure to residents based on the calculation of daily intake (DI) and target hazard quotient (THQ).